Ultra-small multifunctional CoNi-VN nanoparticle composite electrocatalyst as well as preparation method and application thereof
By using ultra-small multifunctional CoNi-VN nanoparticle composite electrocatalyst in electrocatalysts, the problems of high cost, low stability and single functionalization of existing electrocatalysts are solved, and efficient, low-cost and stable multifunctional catalytic performance is achieved.
Patent Information
- Application Number
- CN202510060318.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-15
AI Technical Summary
Existing electrocatalysts have problems such as high cost, low stability, nanoparticle aggregation, insufficient microenvironment regulation and single functionalization, which limits their wide application in the fields of water decomposition and metal air batteries.
Ultra-small multifunctional CoNi-VN nanoparticle composite electrocatalyst is used, and PEI is used as a soft template and polyoxygenate is used as a precursor to prevent the aggregation of catalyst particles, and CoNi and VN materials are embedded in N and B co-doped carbon nanotubes to enhance the stability and catalytic performance of the catalyst.
It achieves efficient, low-cost and stable multifunctional catalytic performance, overcomes the problems of insufficient nanoparticle aggregation and stability, and improves the kinetic performance and long-term stability of the catalyst.
Smart Images

Figure CN119890333A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanomaterials, and in particular to an ultra-small multifunctional CoNi-VN nanoparticle composite electrocatalyst and a preparation method and application thereof. Background Art
[0002] The rapid growth of global energy demand and increasing environmental pressure urgently require the development of sustainable energy conversion and storage technologies. Electrochemical technologies, such as water splitting to produce hydrogen and metal-air batteries, have become the core of clean energy systems. However, the core reactions involved in these technologies, including hydrogen evolution reaction (HER), oxygen evolution reaction (OER) and oxygen reduction reaction (ORR), face the dual challenges of slow reaction kinetics and high thermodynamic energy barriers. Traditional precious metal catalysts (such as platinum (Pt), ruthenium (Ru), iridium (Ir)) have excellent catalytic activity, but their high cost, scarcity and poor durability limit their large-scale application. In addition, traditional electrocatalysts usually focus on a single electrochemical reaction, which increases the complexity and manufacturing cost of the system. Therefore, the development of efficient, low-cost and stable multifunctional catalysts is crucial to breaking through the above bottlenecks.
[0003] Enhancing electron transport, ion concentration, and active site enrichment near the catalytic center is an effective strategy to improve catalytic activity, which can promote catalytic reactions kinetically and thermodynamically. Strong local electric fields (LEFs) enhance electron transport and ion adsorption near the active sites, significantly improve the adsorption / desorption behavior of intermediates, and regulate the microenvironment of the reaction, thereby accelerating the multi-electron reduction process. Catalysts with high curvature structures generate strong local electric fields and high surface ion concentrations, which facilitate proton-coupled electron transfer and reduce the thermodynamic energy barrier of the reaction path. In addition, rationally designed nanostructures and heteroatom doping can regulate the electronic state of active sites, making the bond breaking and adsorption processes of intermediates more efficient. Vanadium nitride (VN) has attracted widespread attention due to its precious metal-like electronic state, excellent electrical conductivity, and high catalytic activity. Cobalt-nickel alloy (CoNi) provides significant intrinsic catalytic activity and promotes HER, OER, and ORR reactions by regulating the electronic structure and composition ratio. Therefore, material design that combines microenvironmental control with intrinsic material properties is crucial to overcome these limitations. Although the existing metal electrocatalysts have good catalytic performance in theory, they have the following significant defects in practical applications:
[0004] 1. Poor stability of non-precious metal catalysts:
[0005] Although some progress has been made in the research of non-precious metal materials such as VN and CoNi, these materials are prone to side reactions under high current density or extreme environment. For example, VN is prone to side reactions with electrolytes under acidic or alkaline conditions, causing the catalyst to transform into oxides, which seriously affects the catalytic performance and stability. In addition, cobalt-nickel alloy catalysts are also prone to structural changes at high temperature or high current density, further reducing their catalytic effect.
[0006] 2. Nanoparticle aggregation problem:
[0007] In the prior art, although researchers have tried to increase the exposure rate of active sites by controlling the particle size of the catalyst, VN nanoparticles tend to aggregate during the synthesis process, resulting in increased particle size and reduced exposure of active sites. Aggregated nanoparticles not only reduce the reactivity of the catalyst, but also cause the catalyst to become less stable after long-term use.
[0008] 3. Insufficient regulation of catalyst microenvironment:
[0009] Although the LEFs effect has been shown to play an important role in improving electrocatalytic performance, existing catalyst designs often do not effectively regulate the electric field strength between the catalyst surface and the electrolyte. Conventional catalysts usually do not accelerate electron transport, improve ion enrichment, or optimize the adsorption / desorption behavior of intermediates through reasonable microenvironment regulation, thereby limiting the rate of multi-electron reactions.
[0010] 4. Limitations of single-function catalysts:
[0011] Many current catalysts usually focus on a single electrocatalytic reaction (such as only one reaction in HER, OER or ORR), but cannot provide efficient catalytic performance in different electrochemical reactions. Such single-function catalysts increase the complexity and manufacturing cost of the system, which is not conducive to achieving large-scale, low-cost energy conversion and storage.
[0012] 5. High cost and resource scarcity of precious metal catalysts:
[0013] Although noble metal catalysts (such as Pt, Ru, Ir, etc.) have excellent catalytic performance, their practical application is limited due to their high cost, scarcity, and unsustainability in large-scale applications. In order to cope with the large-scale demand for energy conversion and storage technologies, it is urgent to find low-cost and more stable alternative materials.
[0014] In summary, catalysts in the existing technology have problems such as high cost, low stability, nanoparticle aggregation, insufficient microenvironment regulation and single functionalization. These defects seriously limit the wide application of catalysts in fields such as water splitting and metal-air batteries. Summary of the invention
[0015] The purpose of the present invention is to provide a new type of electrocatalyst that can effectively overcome the problems existing in the above-mentioned prior art.
[0016] In order to achieve the above object, the present invention first provides a method for preparing an ultra-small multifunctional CoNi-VN nanoparticle composite electrocatalyst, the method comprising:
[0017] Step 1: Mix 4.6 mL of H2O and 0.96 mL of C6H 17 N3 mixed to obtain a mixed solvent, 0.1053 g NH4VO3, 0.29 g Co(NO3)2·6H2O, 0.2846 g H3BO3 and 0.625 g NH4B5O 10 ·4H2O was dissolved in the mixed solvent, stirred for 3 h, and then the solution was transferred to a reactor, heated at 180°C for 72 h, cooled to room temperature at a rate of 10°C / h, ultrasonically treated, washed twice with MeCN, and filtered to obtain a product having a chemical formula of ([Co(H2O)2]3[V 12 O9(OH)9B 18 O 39 (OH)3]·3.5H2O) cobalt-modified boron-vanadium polyoxometalate nanoclusters; named: 3D CoVB;
[0018] Step 2: Mix 0.0421g NH4VO3, 0.05815g Ni(NO3)2·6H2O, 0.1212g H3BO3 and 0.2725g NH4B5O 10 ·4H2O was dissolved in 2mL of H2O, stirred for 3h, and then 0.11mL of ethylenediamine was added to the mixed solution. Subsequently, the solution was transferred to a reactor, heated at 180°C for 7 days, cooled to room temperature naturally, treated with ultrasound, washed twice with MeCN, and filtered to obtain a product with the chemical formula ([Ni(H2O)2]3[V 12 O9(OH)9B 18 O 39 (OH)3]·3.5H2O) nickel-modified boron-vanadium polyoxometalate nanoclusters; named: 3D NiVB;
[0019] Step 3: 0.0421g NH4VO3, 0.026g Ni(NO3)2·6H2O, 0.026g Co(NO3)2·6H2O, 0.1212g H3BO3 and 0.2725g NH4B5O 10·4H2O was dissolved in 2mL of H2O, stirred for 3h, and then 0.11mL of ethylenediamine was added to the mixed solution. Subsequently, the solution was transferred to a reactor, heated at 180°C for 7 days, cooled naturally to room temperature, ultrasonically treated, washed twice with MeCN, and filtered to obtain a chemical formula: ([Co 0.5 Ni 0.5 Ni(H2O)2]3[V 12 O9(OH)9B 18 O 39 (OH)3]·3.5H2O) cobalt-nickel bimetallic modified boron-vanadium polyoxometalate nanoclusters; named: 3D CoNiVB;
[0020] Step 4: 10 g of PEI was dissolved in 10 mL of deionized water, and then 50 mg of 3DCoNiVB prepared in step 3 was added. The resulting mixture was continuously heated in a crucible until the water was removed. Finally, the mixture was heated in an Ar atmosphere at 5 °C min -1 The heating rate was heated to 800°C and maintained for 2 h to obtain a CoNi-VN nanoparticle composite electrocatalyst named: CoNi / VN / BNCNT.
[0021] Preferably, the cobalt-modified boron-vanadium polyoxometalate nanoclusters prepared in the above step 1 have a crystal space group of cubic Pn-3, and unit cell parameters of α=90°, β=90°, γ=90°,
[0022] In addition, the present invention also provides a CoNi-VN nanoparticle composite electrocatalyst prepared by the above preparation method.
[0023] Finally, the present invention also provides the use of the CoNi-VN nanoparticle composite electrocatalyst in hydrogen evolution reaction, oxygen evolution reaction or oxygen reduction reaction.
[0024] Beneficial effects of the present invention
[0025] The present invention provides a novel electrocatalyst having the following advantages:
[0026] 1. Overcoming the problem of nanoparticle aggregation: Through innovative design, the present invention uses polyethyleneimine (PEI) as a soft template and polyoxometalates (POMs) as precursors, which effectively prevents the aggregation of catalyst particles during the synthesis process and ensures the uniform distribution of nanoparticles at the nanoscale, thereby improving the active site exposure rate and catalytic performance of the catalyst.
[0027] 2. Improve the stability of the catalyst: The catalyst system of the present invention combines CoNi and VN materials and embeds them into N, B co-doped carbon nanotubes. The nano-confinement effect is used to effectively enhance the geometric stability of the catalyst, avoiding side reactions or structural changes under high current density or extreme environment, thereby ensuring long-term catalytic stability.
[0028] 3. Enhanced local electric field effect: The present invention successfully prepared ultra-small CoNi and VN nanoparticles with a particle size of about 4nm. These ultra-small particles have a large specific surface area and high curvature, and can generate strong LEFs in the catalytic center. This local electric field can effectively improve the electron transfer efficiency and ion enrichment, thereby accelerating the rate of multi-electron reduction reactions and improving the kinetic performance of catalytic reactions.
[0029] 4. Realize multifunctional catalysis: The catalyst designed in the present invention can not only effectively promote HER, OER and ORR, but also has efficient trifunctional catalytic performance, overcoming the problem that existing catalysts can only be optimized for a single reaction, thereby reducing system complexity and manufacturing costs.
[0030] Through the above design, the present invention aims to provide a highly efficient, low-cost and stable multifunctional electrocatalyst, which can provide excellent electrocatalytic performance in fields such as water decomposition and zinc-air batteries, and significantly improve the long-term stability of the catalyst, thereby promoting the development of clean energy conversion and storage technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagrams of the structures of 3D CoBV and 3D NiBV clusters provided by the present invention, wherein Figures a and b are ball-and-stick models of 3D CoBV and 3D NiBV clusters, respectively; Figures c and d are crystal stacking structure views of 3D CoBV and 3D NiBV clusters, respectively;
[0032] Figure 2 V6O in the crystal structure of 3D CoBV provided by the present invention 18 and V 12 O 60 Schematic diagram of the cluster structure and the coordination diagram of Co atoms, where Figure a is V6O 18 Schematic diagram of cluster; Figure b is B 18 Ring connected V 12 O 60 Ball-and-stick diagram of the cluster; Figure c is a schematic diagram of the coordination of Co atoms; Figure d is a crystal stacking view of 3D CoBV;
[0033] Figure 3The structural characterization diagrams of 3D CoBV, 3D NiBV and 3D CoNiBV provided by the present invention, wherein Figure a is the XRD diagram of 3D CoBV, 3D NiBV and 3D CoNiBV; Figure b is the FT-IR spectrum diagram of 3D CoBV, 3D NiBV and 3D CoNiBV;
[0034] Figure 4 The morphology characterization diagram of the CoNi / VN / BNCNT composite catalyst provided by the present invention, wherein Figures a and b are TEM images of CoNi / VN / BNCNT; Figure c is a particle size distribution diagram of CoNi and VN; Figures d, e, and f are HRTEM images of CoNi / VN / BNCNT;
[0035] Figure 5 The present invention provides a structural characterization diagram of the CoNi / VN / BNCNT composite catalyst, wherein Figure a is a PXRD diagram of Ni / VN / BNCNT, Co / VN / BNCNT and CoNi / VN / BNCNT, and the inset in Figure a is a local enlarged diagram of the diffraction spectrum in the range of 43.7° to 45.1°; Figure b is a N2 adsorption-desorption isotherm diagram of Ni / VN / BNCNT, Co / VN / BNCNT and CoNi / VN / BNCNT, and the inset in Figure b is a nanoparticle pore size distribution diagram; Figures c and d are high-resolution Co 2p and Ni2p XPS spectra of CoNi / VN / BNCNT, respectively; Figure e is a relative content diagram of N doping in CoNi / VN / BNCNT, and the inset in Figure e is a high-resolution N1s XPS graph; Figure f is the relative content of B doping in CoNi / VN / BNCNT, where the inset of Figure f is: high-resolution B1s XPS graph of CoNi / VN / BNCNT;
[0036] Figure 6 A high-resolution C1s XPS image of CoNi / VN / BNCNT provided by the present invention;
[0037] Figure 7 A high-resolution V 2p XPS image of CoNi / VN / BNCNT provided by the present invention;
[0038] Figure 8The catalytic performance diagram of CoNi / VN / BNCNT provided by the present invention, wherein Figure a is a HER LSV curve diagram of Ni / VN / BNCNT, Co / VN / BNCNT, and CoNi / VN / BNCNT; Figure b is an OER LSV curve of Ni / VN / BNCNT, Co / VN / BNCNT, and CoNi / VN / BNCNT; Figure c is an RDE LSV curve diagram of Ni / VN / BNCNT, Co / VN / BNCNT, CoNi / VN / BNCNT, and Pt / C at 1600rpm; Figure d is an LSV diagram of CoNi / VN / BNCNT‖CoNi / VN / BNCNT and IrO2‖Pt / C, wherein the inset of Figure d is a photo of a dual-electrode setup; Figure e is a discharge polarization curve and a corresponding power density diagram of CoNi / VN / BNCNT and Pt / C-RuO2; Figure f is a rechargeable Zn-air battery at 10mA cm -2 Long-term cycling performance diagram under current density;
[0039] Fig. 9 The COMSOL simulation electric field distribution diagram provided by the present invention, wherein Figures a1-e1 are respectively the electron field distribution diagrams of BNCNT, VN / BNCNT, CoNi / BNCNT, CoNi / VN / BNCNT-L and CoNi / VN / BNCNT in the HER process; Figures a2-e2 are respectively the electron field distribution diagrams of BNCNT, VN / BNCNT, CoNi / BNCNT, CoNi / VN / BNCNT-L and CoNi / VN / BNCNT in the OER process; Figure f is the electric field intensity and OH of BNCNT, CoNi / VN / BNCNT-L, VN / BNCNT, CoNi / BNCNT and CoNi / VN / BNCNT in the HER and OER processes - Concentration distribution diagram; Figure g is a schematic diagram of the mechanism for improving alkaline water splitting performance;
[0040] Fig.10 COMSOL simulation OH provided by the present invention - Ion concentration distribution diagram, where Figures a1-e1 show OH concentration distribution of BNCNT, CoNi / VN / BNCNT-L, VN / BNCNT, CoNi / BNCNT and CoNi / VN / BNCNT during HER process - Concentration distribution diagram; Figures a2-e2 show OH concentrations of BNCNT, CoNi / VN / BNCNT-L, VN / BNCNT, CoNi / BNCNT and CoNi / VN / BNCNT during the OER process. - Concentration distribution diagram;
[0041] Fig.11The HER, OER and overall water splitting stability performance diagrams of the catalyst provided by the present invention, wherein Figure a is the HER LSV curve of CoNi / VN / BNCNT before and after continuous cycling in 1.0M KOH, wherein the inset of Figure a is the HER LSV curve of CoNi / VN / BNCNT at 10mAcm -2 Figure 1 is a long-term stability test diagram under 10 mA cm-2; Figure b is an OER LSV curve of CoNi / VN / BNCNT before and after continuous cycling in 1.0 M KOH, where the inset of Figure b is the OER LSV curve of CoNi / VN / BNCNT under 10 mA cm-2 -2 Figure c is a long-term stability test diagram under a fixed voltage for 15 hours during water decomposition of CoNi / VN / BNCNT; Figure c inset is a graph showing the relationship between the O2 and H2 gas production of CoNi / VN / BNCNT and the reaction time;
[0042] Fig.12 The ORR stability performance diagram of the catalyst provided by the present invention, wherein Figure a is the LSV diagram of CoNi / VN / BNCNT before and after 2000 CV cycles, wherein the inset of Figure a is a long-term stability test diagram of CoNi / VN / BNCNT in an O2-saturated 0.1M KOH solution at 0.85V and 1600rpm; Figure b is a current-time curve of CoNi / VN / BNCNT after adding 1M methanol in 0.1M KOH; DETAILED DESCRIPTION
[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the embodiments of the invention described are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the protection scope of the present invention.
[0044] Secondly, the present invention is described in detail with reference to the accompanying drawings. When describing the embodiments of the present invention in detail, for the convenience of explanation, the accompanying drawings are only examples and should not limit the scope of protection of the present invention.
[0045] The experimental characterization methods described in the following examples are conventional methods unless otherwise specified; the reagents, materials and instruments and equipment described are all commercially available unless otherwise specified.
[0046] The present invention provides a method for preparing an ultra-small multifunctional CoNi-VN nanoparticle composite electrocatalyst based on enhancing a local electric field, and a multifunctional CoNi-VN nanoparticle composite electrocatalyst prepared according to the method, and provides applications of the same in a hydrogen evolution reaction, an oxygen evolution reaction or an oxygen reduction reaction.
[0047] Example 1
[0048] Firstly, a method for preparing an ultra-small multifunctional CoNi-VN nanoparticle composite electrocatalyst is provided, the method comprising:
[0049] Step 1: Mix 4.6 mL of H2O and 0.96 mL of C6H 17 N3 mixed to obtain a mixed solvent, 0.1053 g NH4VO3, 0.29 g Co(NO3)2·6H2O, 0.2846 g H3BO3 and 0.625 g NH4B5O 10 ·4H2O was dissolved in the mixed solvent, stirred for 3 h, and then the solution was transferred to a reactor, heated at 180°C for 72 h, cooled to room temperature at a rate of 10°C / h, ultrasonically treated, washed twice with MeCN, and filtered to obtain a product having a chemical formula of ([Co(H2O)2]3[V 12 O9(OH)9B 18 O 39 (OH)3]·3.5H2O) cobalt-modified boron-vanadium polyoxometalate nanoclusters; named: 3D CoVB;
[0050] Step 2: Mix 0.0421g NH4VO3, 0.05815g Ni(NO3)2·6H2O, 0.1212g H3BO3 and 0.2725g NH4B5O 10 ·4H2O was dissolved in 2mL of H2O, stirred for 3h, and then 0.11mL of ethylenediamine was added to the mixed solution. Subsequently, the solution was transferred to a reactor, heated at 180°C for 7 days, cooled to room temperature naturally, treated with ultrasound, washed twice with MeCN, and filtered to obtain a product with the chemical formula ([Ni(H2O)2]3[V 12 O9(OH)9B 18 O 39 (OH)3]·3.5H2O) nickel-modified boron-vanadium polyoxometalate nanoclusters; named: 3D NiVB;
[0051] Step 3: 0.0421g NH4VO3, 0.026g Ni(NO3)2·6H2O, 0.026g Co(NO3)2·6H2O, 0.1212g H3BO3 and 0.2725g NH4B5O 10 ·4H2O was dissolved in 2mL of H2O, stirred for 3h, and then 0.11mL of ethylenediamine was added to the mixed solution. Subsequently, the solution was transferred to a reactor, heated at 180°C for 7 days, cooled naturally to room temperature, ultrasonically treated, washed twice with MeCN, and filtered to obtain a chemical formula: ([Co 0.5 Ni 0.5 Ni(H2O)2]3[V 12 O9(OH)9B18 O 39 (OH)3]·3.5H2O) cobalt-nickel bimetallic modified boron-vanadium polyoxometalate nanoclusters; named: 3D CoNiVB;
[0052] Step 4: Dissolve 10 g of positively charged PEI in 10 mL of deionized water, then add 50 mg of negatively charged 3D CoNiVB prepared in step 3. The resulting mixture is continuously heated in a crucible until the water is removed to obtain a black colloidal state. Finally, heat the mixture in an Ar atmosphere at 5 °C min -1 The heating rate was heated to 800°C and maintained for 2 h to obtain a CoNi-VN nanoparticle composite electrocatalyst named: CoNi / VN / BNCNT.
[0053] The reagents used in the above preparation method were all purchased from the market. The reagents used, specifications and manufacturers are shown in Table 1.
[0054] Table 1
[0055]
[0056]
[0057] The present application provides a CoNi / VN / BNCNT catalyst material containing cobalt-nickel alloy nanoparticles. To demonstrate its catalytic performance and stability, Co / VN / BNCNT and Ni / VN / BNCNT were prepared for performance comparison.
[0058] Comparative Example 1
[0059] According to the preparation method described in step 1 of Example 1, 3D CoVB is prepared for use; 10 g of positively charged PEI is dissolved in 10 mL of deionized water, and then 50 mg of the negatively charged 3D CoVB prepared above is added, and the obtained mixture is continuously heated in a crucible until the water is removed to obtain a black colloidal state; finally, in an Ar atmosphere at 5 ° C min -1 The heating rate was heated to 800°C and maintained for 2 h to obtain a multifunctional electrocatalyst composite material named: Co / VN / BNCNT.
[0060] Comparative Example 2
[0061] According to the preparation method described in step 2 of Example 1, 3D NiVB is prepared for use; 10 g of positively charged PEI is dissolved in 10 mL of deionized water, and then 50 mg of the negatively charged 3D NiVB prepared above is added, and the obtained mixture is continuously heated in a crucible until the water is removed to obtain a black colloidal state; finally, in an Ar atmosphere at 5 ° C min -1The heating rate was heated to 800 °C and maintained for 2 h to obtain a multifunctional electrocatalyst composite material named Ni / VN / BNCNT.
[0062] Single crystal X-ray diffraction analysis shows that the 3D CoVB, 3D NiVB and 3D CoNiVB compounds prepared in Example 1 are isostructural, and each compound crystallizes in the cubic Pn-3 space group (e.g. Figure 1 ). The crystal structure of 3D CoVB is used as a representative for description, as shown in Figure 2 As shown in a, oxygen atoms bridge six VO5 square pyramids to form a V6 cluster. Two V6 clusters are arranged face to face, and V is formed by bridging B and O atoms. 12 cluster, while V 12 The cluster is composed of six [B3O7] units. 18 Surrounded by a ring. Figure 2 As shown in Figure b, two B atoms adopt tetrahedral coordination in the [B3O7] unit, while one B atom adopts planar trigonal coordination. Figure 2 c, the adjacent V 12 B 18 The clusters are connected by six-coordinated Co ions, four of which come from oxygen atoms in the cluster and two from water molecules. Finally, the structure extends along the a, b, and c crystal axes to form a V-based 12 B 18 The three-dimensional open framework of the cluster unit has the chemical formula [Co(H2O)2]3[V 12 O9(OH)9B 18 O 39 (OH)3]·3.5H2O, such as Figure 2 d, and its crystal data are shown in Table 2.
[0063] Table 2
[0064]
[0065]
[0066] Characterization of 3D NiVB crystals
[0067] The phase purity of the compounds was determined by powder X-ray diffraction (PXRD) analysis. Figure 3 As shown in a, the simulated curves are highly matched with the experimental curves, indicating that 3D NiVB, 3D CoVB, and 3D CoNiVB have high crystallinity and purity. The chemical composition of the obtained compounds was further analyzed by Fourier transform infrared spectroscopy (FT-IR). Figure 3As shown in b, the FT-IR spectrum shows the typical features of POMs spectrum, in which the stretching vibration band of metal-oxygen bond appears in the range of 500–1200 cm -1 The asymmetric stretching vibration of the V–O–B group appears at about 457 cm -1 . Appears at 790, 717 and 664 cm -1 The signals correspond to the symmetric and asymmetric stretching vibrations of V–O–V. -1 and 1060-1070cm -1 The peaks observed at 1671, 1600 and 3461–2947 cm-1 are associated with the B–O stretching vibrations in the [BO3] and [BO4] units. -1 The signals at are attributed to the N–H bonds and O–H groups, respectively.
[0068] Catalyst CoNi / VN / BNCNT characterization
[0069] like Figure 4 Transmission electron microscopy (TEM) images show that the CoNi / VN / BNCNT material exhibits a hollow bamboo-like carbon nanotube structure ( Figure 4 a). This three-dimensional layered morphology facilitates rapid penetration of electrolytes into electrocatalytic active sites, thereby improving reaction efficiency. Figure 4 b and Figure 4 c shows metallic Co and VN nanoclusters with an average diameter of 4 nm, uniformly dispersed and embedded in carbon nanotubes without significant aggregation, which helps to maintain high structural stability and durability in alkaline electrolytes. Figure 4 df High-resolution TEM (HRTEM) images show that the (111) planes of CoNi and VN have spacings of 0.204 and 0.242 nm, respectively. In addition, the spacing of the graphite C (002) lattice is 0.351 nm, indicating the high crystallinity of carbon nanotubes in CoNi / VN / BNCNT.
[0070] Figure 5 a shows that the PXRD spectrum of CoNi / VN / BNCNT is very similar to the spectra of Co / VN / BNCNT and Ni / VN / BNCNT samples. The diffraction peaks at 44.3°, 51.6°, and 76.0° correspond to the characteristic (111), (200), and (220) planes of CoNi alloy, respectively, while the broad peak at 26.2° indicates the presence of graphitic carbon. In addition, the diffraction peaks at 37.7°, 43.7°, 63.5°, and 76.2° are related to the cubic VN structure. Among them, Figure 5The inset of a presents a local enlargement of the diffraction pattern from 43.7° to 45.1°, showing that the CoNi (111) diffraction peak is located between the diffraction peaks of pure cobalt (PDF#15-0806) and nickel (PDF#04-0850). This indicates that the alloying of Co and Ni leads to lattice expansion, confirming the formation of CoNi.
[0071] like Figure 5 The nitrogen adsorption-desorption isotherm shown in b shows that the Ni / VN / BNCNT (213.1 m 2 / g) and Co / VN / BNCNT(165.3m 2 / g), CoNi / VN / BNCNT has the highest specific surface area, reaching 630.8 m 2 / g. Figure 2 As shown in (b), the pore size distribution shows that the pore size ranges from 2 to 10 nm, which is consistent with the nitrogen isotherm results. The mesoporous structure and high surface area of CoNi / VN / BNCNT can promote electrolyte penetration and facilitate electrolyte diffusion to the active sites. In addition, large volume changes during charge and discharge can also be effectively alleviated.
[0072] The composition and valence state of the electrocatalysts were analyzed by X-ray photoelectron spectroscopy (XPS). Figure 6 As shown in Figure 2, in CoNi / VN / BNCNT, carbon species are represented by five different peaks (283.5, 284.8, 285.5, 286.5, and 288.0 eV), which correspond to different C–B, C–C, C–N, C–N / C–O, and COO– groups, respectively. Figure 7 As shown, V2p 3 / 2 The XPS spectrum shows peaks at 513.78, 515.5, and 517.3 eV, indicating the presence of V–N, V–N–O, and V–O species. Figure 5 c) shows three chemical states of cobalt, including metallic Co, Co 2+ and Co 3+ The peaks at 777.9 eV and 792.9 eV are from Co–Co bonds, while slight surface oxidation leads to Co peaks at 779.7 eV and 794.7 eV. 3+ signal, and Co at 781.5 eV and 796.5 eV 2+ signal. Similarly, through Ni 2p 3 / 2 Peak deconvolution, Ni 0 、Ni 2+ and Ni 3+ They appear at 852.27eV, 854.13eV and 855.27eV respectively ( Figure 5d) The formation of CoNi alloy nanoparticles is further carried out by metal Co 0 and Ni 0 The existence of Co in CoNi / VN / BNCNT is confirmed, which is completely consistent with the XRD results. 0 2p 3 / 2 Peak ratio Co / VN / BNCNT Co 0 2p 3 / 2 The binding energy of the peak is about 0.3 eV lower. 0 2p 3 / 2 Peak relative to Ni / VN / BNCNT 0 2p 3 / 2 The peak shows a positive shift of about 0.3 eV. These observations suggest that the incorporation of Ni affects the electronic structure of Co, highlighting the synergistic effect between the two metals. In CoNi, cobalt atoms are able to gain d electrons from neighboring nickel atoms, which act as electron donors. The N 1s XPS spectrum shows seven peaks representing V–N (397.5 eV), B–N–C (398.3 eV), pyridinic nitrogen (398.9 eV), Co / Ni–N4 (399.8 eV), pyrrolic nitrogen (400.6 eV), graphitic nitrogen (401.2 eV), and oxidized nitrogen (402.2 eV). Histogram of nitrogen species ( Figure 5 e) shows abundant active nitrogen species, especially pyridinic nitrogen (14.6%), graphitic nitrogen (16.81%) and Co / Ni–N4 (14.6%). Pyridinic nitrogen affects the electronic structure of surrounding carbon atoms, affecting the spin and current density, as well as the p-state density at the Fermi level, thus affecting the overall surface and electronic properties of the carbon material. Co / Ni–N4 acts as a catalytic anchor point to optimize the adsorption energy and accelerate the electrochemical reaction. Graphitic nitrogen enhances the limiting current density in the ORR process by promoting the adsorption of oxygen and dissociation of intermediates. Figure 5 f, the B 1s XPS spectrum can be decomposed into four peaks located at 189.5, 190.8, 191.4, and 192.5 eV, corresponding to BC3, B–N, BC2O, and BCO2. The graphite-like structure of the active BC3 species represents an important active site for ORR. The B–N species is crucial to improving the catalytic activity through the strong charge transfer effect between the adjacent C atoms.
[0073] In addition, in this study, the trifunctional catalytic performance of the catalyst was analyzed using a classic three-electrode system. Figure 8As shown in a, the HER linear sweep voltammetry (LSV) curves of CoNi / VN / BNCNT were compared with the samples prepared in Comparative Examples 1 and 2. The data show that CoNi / VN / BNCNT only needs an overpotential of 109 mV to reach 10 mA cm -2 In comparison, the overpotentials of Ni / VN / BNCNT (156 mV) and Co / VN / BNCNT (149 mV) are significantly higher.
[0074] like Figure 8 b) The OER catalytic performance of the catalyst was evaluated by -1 The LSV test was performed in KOH solution to evaluate and compare the performance. The CoNi / VN / BNCNT catalyst only required an overpotential of 362 mV to achieve 50 mA cm -2 The current density is better than that of Ni / VN / BNCNT (396 mV) and Co / VN / BNCNT (386 mV), as well as other reported catalysts (as shown in Table 3).
[0075] Table 3
[0076]
[0077]
[0078] The ORR activity of CoNi / VN / BNCNT was analyzed in an O2-saturated 0.1 M KOH solution at a rotation speed of 1600 rpm. Figure 8 c shows that CoNi / VN / BNCNT has a more positive onset potential (Eonset, 1 V) and half-wave potential (Eonset, 1 V) compared with Ni / VN / BNCNT, Co / VN / BNCNT, and Pt / C. 1 / 2 , 0.85V).
[0079] Inspired by the excellent catalytic performance of CoNi / VN / BNCNT in HER and OER, a dual-electrode system was constructed to promote the overall water splitting reaction. Figure 8 As shown in d, CoNi / VN / BNCNT only needs 1.52 V to achieve 10 mA cm -2 The current density can reach 50mA cm at 1.67V. -2 , which are significantly lower than IrO2||Pt / C (1.57 V and 1.78 V, respectively), and are superior to most of the multifunctional electrocatalysts reported so far (Table 4).
[0080] Table 4
[0081]
[0082]
[0083] Due to the excellent catalytic performance of CoNi / VN / BNCNT in OER and ORR, zinc-air batteries were constructed. Figure 8 As shown in e, the zinc-air battery based on CoNi / VN / BNCNT is -2 At a current density of 220 mW cm -2 The peak power density is about the same as that of zinc-air batteries using Pt / C-RuO2 (160 mW cm -2 , 108mA cm -2 ) and outperforms the performance of recently reported electrocatalysts in zinc-air batteries (Table 5). Figure 8 f, by applying 10 mA cm -2 The constant current charge and discharge test was carried out to verify the stability and long-term charge and discharge capability of the battery. When the initial discharge voltage of the CoNi / VN / BNCNT-based zinc-air battery was 1.17V, the charge voltage was 2.06V, and the charge and discharge voltage difference was 0.89V, after 1000 long-term tests (20 minutes per cycle), the charge and discharge voltage difference only increased by 0.94V, with a growth rate of less than 5%. Overall, these results show that the CoNi / VN / BNCNT electrocatalyst has great potential for application in rechargeable zinc-air batteries due to its excellent electrocatalytic reactivity and stability.
[0084] Table 5
[0085]
[0086]
[0087] To explore the potential mechanism behind the excellent electrocatalytic performance, this study used COMSOL Multiphysics simulation to analyze the charge and ion distribution near the catalyst surface. Two-dimensional models with different particle sizes and compositions were constructed to represent the electrodes immersed in 1.0 M KOH electrolyte. Fig. 9 b and Fig. 9 As shown in Fig. 3c, there are high electric field regions (marked in red) around each CoNi and VN nanoparticle modified on the BNCNT surface. These hot spots are evenly distributed on the electrode surface, significantly affecting the reaction kinetics and serving as a major contributor to improving the overall catalytic efficiency. In addition, these hot spots expand the effective reaction surface area of the BNCNT, providing more sites for the interaction between reactants and catalysts. Fig.10 As shown in Figure 2, during the HER and OER processes, OH around CoNi and VN nanoparticles -The concentration of OH was significantly increased. This indicates that the local electric field generated by the nanoparticles plays a crucial role in promoting the ion concentration gradient required for efficient catalysis. The BNCNT structure loaded with CoNi or VN nanoparticles showed a stronger local electric field than pure BNCNT, and the OH - The repulsion of ions is stronger, indicating that H + The enrichment of OH is enhanced. - Simulation data summary of concentration and electric field strength, combined with Fig. 9 As shown in f, the simulation results further show that the electric field strength near the CoNi / VN / BNCNT surface can reach 0.04V / μm, and OH - The concentration of OH was 0.96 mol / L. Similar ion enhancement effects were also observed in the OER process. It is worth noting that in the HER process, as the electric field strength increases, the OH - The concentration of OH in OER decreased, while under the same conditions - To study the effect of nanoparticle size, a model was constructed in which the BNCNT surface was coated with larger nanoparticles (about 100 nm) synthesized by conventional methods. Fig. 9 d and Fig. 9 As shown in e, computational finite element simulations show that the 4 nm CoNi-VN nanoparticles generate a local electric field 2.1 times stronger than larger nanoparticles. This enhanced local electric field creates an ion-rich environment that promotes the adsorption and activation of key species (e.g. Fig. 9 g), ultimately improving the catalytic performance.
[0088] Table 6
[0089]
[0090] like Fig.11 As shown in Figure a, the current density of CoNi / VN / BNCNT remained relatively stable after 12 hours without obvious attenuation. The overpotential of the LSV curve after 2000 CV cycles increased by only 2 mV, further confirming the excellent durability of CoNi / VN / BNCNT catalyst in HER.
[0091] In the OER stability test, CoNi / VN / BNCNT maintained a relatively stable current density after 12 hours of continuous reaction, without significant increase. Fig.11 As shown in b, after 2000 CV tests, the CoNi / VN / BNCNT catalyst only showed an activity loss of about 11 mV, showing good electrochemical stability.
[0092] like Fig.11 As shown in c, the current density of the constructed CoNi / VN / BNCNT full water splitting device has almost no decrease after 15 hours, indicating that it has excellent durability. The end of the Faraday efficiency test shows that the linear growth of H2 and O2 gas volumes over time remains stable, and their gas ratio is always about 2:1. The Faraday efficiency of the two gases is close to 100%, indicating that the electrolysis process has almost completed the conversion.
[0093] like Fig.12 As shown in Fig. b, the methanol tolerance test of CoNi / VN / BNCNT and Pt / C was performed by adding 10 mL of methanol to 100 mL of electrolyte. After adding methanol, the current density of Pt / C dropped sharply due to poisoning, while CoNi / VN / BNCNT almost did not lose current, indicating that it has better methanol tolerance. In addition, Fig.12 As shown in the inset of a, after continuous reaction at 0.85 V for 10 hours, the current density of CoNi / VN / BNCNT remained at 93.95%. Fig.12 As shown in a, after 1000 CV cycle tests, the E 1 / 2 Only a shift of about 2 mV occurred. These two results indicate the excellent durability of CoNi / VN / BNCNT in ORR.
[0094] In summary, this study successfully designed and synthesized Co / Ni modified boron vanadium polyoxometalates, and prepared CoNi and VN nanodots encapsulated in B- and N-doped carbon nanotubes as trifunctional electrocatalysts by PEI soft template method. This strategy effectively solved the problem of nanoparticle aggregation by utilizing the electrostatic interaction between PEI and POMs, and achieved uniform dispersion and controllable particle size. COMSOL simulation results show that the BNCNT structure loaded with CoNi or VN nanoparticles exhibits stronger local electric fields, which contribute to the enhanced adsorption of reaction intermediates compared with pure BNCNT. In a strong LEFs environment, coupled with the high specific surface area and efficient charge transfer characteristics of the carbon nanotube structure, the catalytic activity of CoNi / VN / BNCNT in HER, OER and ORR is excellent, reaching a level comparable to that of precious metal catalysts. In the overall water splitting reaction, CoNi / VN / BNCNT achieved 50mA cm at a low applied voltage of 1.67V. -2 The current density is better than that of most non-precious metal electrocatalysts. In addition, the CoNi / VN / BNCNT-based rechargeable zinc-air battery showed excellent performance with a peak power density of 220mWcm -2 , with a specific capacity of 810 mAh g -1 , and at 10mA cm -2The cycling stability exceeds 1000 cycles, surpassing the performance of Pt / C-RuO2-based zinc-air batteries.
Claims
1. A method for preparing an ultra-small multifunctional CoNi-VN nanoparticle composite electrocatalyst, characterized in that: The method includes: Step 1: Mix 4.6 mL of H2O and 0.96 mL of C6H 17 N3 mixed to obtain a mixed solvent, 0.1053g NH4VO3, 0.29g Co(NO3)2·6H2O, 0.2846g H3BO3 and 0.625g NH4B5O 10 ·4H2O was dissolved in the mixed solvent, stirred for 3 h, and then the solution was transferred to a reactor, heated at 180°C for 72 h, cooled to room temperature at a rate of 10°C / h, ultrasonically treated, washed twice with MeCN, and filtered to obtain a product having a chemical formula of ([Co(H2O)2]3[V 12 O9(OH)9B 18 O 39 (OH)3]·3.5H2O) cobalt-modified boron-vanadium polyoxometalate nanoclusters; named: 3D CoVB; Step 2: Mix 0.0421g NH4VO3, 0.05815g Ni(NO3)2·6H2O, 0.1212g H3BO3 and 0.2725g NH4B5O 10 ·4H2O was dissolved in 2mL of H2O, stirred for 3h, and then 0.11mL of ethylenediamine was added to the mixed solution. Subsequently, the solution was transferred to a reactor, heated at 180°C for 7 days, cooled to room temperature naturally, treated with ultrasound, washed twice with MeCN, and filtered to obtain a product with the chemical formula ([Ni(H2O)2]3[V 12 O9(OH)9B 18 O 39 (OH)3]·3.5H2O) nickel-modified boron-vanadium polyoxometalate nanoclusters; named: 3D NiVB; Step 3: 0.0421g NH4VO3, 0.026g Ni(NO3)2·6H2O, 0.026g Co(NO3)2·6H2O, 0.1212g H3BO3 and 0.2725g NH4B5O 10 ·4H2O was dissolved in 2mL of H2O, stirred for 3h, and then 0.11mL of ethylenediamine was added to the mixed solution. Subsequently, the solution was transferred to a reactor, heated at 180°C for 7 days, cooled naturally to room temperature, ultrasonically treated, washed twice with MeCN, and filtered to obtain a chemical formula: ([Co 0.5 Ni 0.5 Ni(H2O)2]3[V 12 O9(OH)9B 18 O 39 (OH)3]·3.5H2O) cobalt-nickel bimetallic modified boron-vanadium polyoxometalate nanoclusters; named: 3D CoNiVB; Step 4: 10 g of PEI was dissolved in 10 mL of deionized water, and then 50 mg of 3DCoNiVB prepared in step 3 was added. The resulting mixture was continuously heated in a crucible until the water was removed. Finally, the mixture was heated in an Ar atmosphere at 5 °C min -1 The heating rate was heated to 800°C and maintained for 2 h to obtain a CoNi-VN nanoparticle composite electrocatalyst named: CoNi / VN / BNCNT.
2. The method for preparing an ultra-small CoNi-VN nanoparticle composite electrocatalyst according to claim 1, characterized in that: The cobalt-modified boron-vanadium polyoxometalate nanoclusters prepared in step 1 have a crystal space group of cubic Pn-3 and unit cell parameters of α=90°, β=90°, γ=90°.
3. A CoNi-VN nanoparticle composite electrocatalyst prepared according to the preparation method according to claim 1.
4. Use of the CoNi-VN nanoparticle composite electrocatalyst according to claim 3 in hydrogen evolution reaction, oxygen evolution reaction or oxygen reduction reaction.
Citation Information
Patent Citations
MOFs (Metal Organic Frameworks)-based NiCo@N-C dual-function oxygen electrode catalyst and preparation method thereof
CN108722460A
Nitrogen-doped carbon nanotube coated CoNi nano-alloy catalyst as well as preparation method and application thereof
CN115478293A
CoNi alloy loaded nanofiber / nanotube coupled multilevel structure as well as preparation method and application thereof
CN116387539A